Reformulasi Konsep Pengampuan Melalui Penguatan Pengawasan oleh Pengampu Pengawas - Fouziah, Resti; Hadi, Syofyan (Journal Evidence Of Law, 2025)
The concept of guardianship in the Civil Code (KUH Perdata) has so far contained a discriminatory approach towards people with mental and/or intellectual disabilities. This is reflected in the use of terms such as "stupid", "brain disease", and "dark eyes", as well as the provisions of Article 433 of the Civil Code which require the determination of guardianship without considering individual capacity. Constitutional Court Decision Number 93/PUU-XX/2022 is present as a constitutional correction that encourages a change in approach, from a generalized guardianship model to an assessment based on personal capacity. This study aims to analyze the urgency of reformulating the concept of guardianship so that it is in line with the principles of non-discrimination and respect for the rights of people with disabilities as regulated in Law Number 8 of 2016 and the Convention on the Rights of Persons with Disabilities (CRPD). Through a normative legal approach, this article recommends strengthening the role of supervisory guardians in guardianship institutions consisting of various professional elements to realize protection for people under guardianship/ curandus. The results of this study indicate that the concept of guardianship, as regulated by the laws and regulations in Indonesia, still has weaknesses in terms of oversight of the actions and policies taken by guardians toward the individuals under their care. The absence of a strong supervisory mechanism opens opportunities for abuse of authority, both administratively and financially, which can harm the interests of the protected individuals.